Kewirausahaan Sebagai Solusi Pemberdayaan Ekonomi Masyarakat di Desa Dolok Kahean (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) from the University of Muhammadiyah North Sumatra in 2025 took place in Dolok Kahean Village, Tapian Dolok District, Simalungun Regency, with the theme "Entrepreneurship as a Solution for Community Economic Empowerment. " The main objective of this activity was to improve the competence of Micro, Small, and Medium Enterprises (MSMEs) by implementing digital marketing strategies and strengthening local product brands, especially rengginang businesses. The methods applied included observation, interviews, socialization, and participatory training. The core program included logo and product identity creation, photography training and promotional content editing, social media account creation, and education on Go Digital Safe for the community. The results of this activity showed an increase in the skills of MSMEs in using digital media for promotion, expanding market share, and increasing product competitiveness. In addition, students gained practical insights in the application of entrepreneurship, communication, and social project management. The main challenges faced, namely the lack of internet access and low digital literacy in the community, can be overcome through a direct approach and intensive mentoring. Overall, the KKN program has been successful in strengthening collaboration between higher education institutions and the community and has become an example of digital-based economic empowerment at the village level.